An Experimental Study on Concrete Durability using Bubble Wrap (LDPE) as Partial Coarse Aggregate of Concrete - Norlihan, Muhamad Hasif; Adnan, Suraya Hani (Progress in Engineering Application and Technology, 2024)
In this research, bubble wrap is used to improve performance of concrete in terms of durability. It is essential to define optimum percentage properly and optimally during the laboratory process to improve durability of the concrete samples. Since bubble wrap has been used globally for packaging, based on previous study there are several problems that occur in recycling centre and environment are frequently caused by plastic waste. The main objective of this study is to determine concrete performance with bubble wrap that contain light-density polyethylene (LDPE) as partial replacement coarse aggregate. Besides, this research investigates the physical properties of coarse aggregate of LDPE by conducting slump at each type of replacement samples involve in this project. Next, to study the water absorption of concrete with coarse aggregate of LDPE and to determine carbonation depth of concrete surface that partially mix with LDPE. In addition, it can increase durability with quality when replacing gravel with LDPE replacement aggregates. Water absorption and carbonation depth test has been conducted for the comparison of conventional concrete and replacement concrete. From there, it can be shown that LDPE aggregates helps decrease water absorption and carbonation depth of the samples and it is experimentally proved better than control samples. Other than that, slump test is the variables that were valuated which is three different type of slump such as true slump, shear slump and zero slump to define the best percentage of replacement aggregates on concrete. As a result, the 5% LDPE aggregates has a greater impact on concrete durability. Based on the outcomes of the experiment, by increasing the LDPE aggregates replacement on concrete can affect the water absorption and carbonation depth, the workability of the samples is the most significant element impacting the integrity of a concrete.